Konsep Riba Jual Beli Kredit - M. Raihan Amri; Rizka Amelia (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2026)
Riba, in the context of credit transactions, refers to the practice of charging or receiving interest or additional profit in buying and selling transactions with a credit system. In Islamic terminology, riba is prohibited because it is considered unjust and violates the principles of justice and equality in economic transactions. In Islam, financial concepts and transactions are governed by Sharia principles that prohibit riba (interest), gharar (uncertainty), and unfair practices. When discussing credit cards in Islam, there are differing opinions among scholars. Some scholars consider credit cards to involve riba and gharar, thus making them prohibited in Islam. Riba is forbidden, and credit involving riba is considered haram (forbidden). Muslims are encouraged to stay away from riba and seek halal alternatives in managing their finances.